9(x-8)=3+10x

Simple and best practice solution for 9(x-8)=3+10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-8)=3+10x equation:


Simplifying
9(x + -8) = 3 + 10x

Reorder the terms:
9(-8 + x) = 3 + 10x
(-8 * 9 + x * 9) = 3 + 10x
(-72 + 9x) = 3 + 10x

Solving
-72 + 9x = 3 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-72 + 9x + -10x = 3 + 10x + -10x

Combine like terms: 9x + -10x = -1x
-72 + -1x = 3 + 10x + -10x

Combine like terms: 10x + -10x = 0
-72 + -1x = 3 + 0
-72 + -1x = 3

Add '72' to each side of the equation.
-72 + 72 + -1x = 3 + 72

Combine like terms: -72 + 72 = 0
0 + -1x = 3 + 72
-1x = 3 + 72

Combine like terms: 3 + 72 = 75
-1x = 75

Divide each side by '-1'.
x = -75

Simplifying
x = -75

See similar equations:

| 26-12x=96 | | x^2-2x+2/x-1=0 | | 1/2n+7=n+14/2 | | k=h+p+8/3 | | 4y^3+8y^2-y-2=0 | | -9(2-7n)=66-7n | | 1/7(21c-56)=3(c-3/8) | | 3-5(x-6)=48 | | 31/5+b=4/5 | | 4(t+20)=1/5(20t+400) | | 4(x-2)=4x+2 | | 3(x-1)=2(x+8) | | 9x-11=-20 | | -2x+2=-14+6x | | x-3=x-6 | | 3n+40+2n=15 | | 4x+2y+18=0 | | -8x-14=-134 | | -12x=4y-16 | | 1.11=x+3x | | 5x+7(x-1)=-3x | | -1+2x=x-7 | | 2+5=210 | | x-2y-6=10 | | 3x+7-(x+2)=-36 | | 5/17=p/16 | | -1/6+n=1/6 | | -5(6-2n)=45-2n | | logx-log(x-5)=2 | | x-3cosx=0 | | 96=-8(n-8) | | 30x+25y=275 |

Equations solver categories